CORPORATE GOVERNANCE DAN FAKTOR-FAKTOR YANG MEMPENGARUHI KINERJA KEUANGAN - Lucia Ari Diyani; Gizela Giovani Kusumah (Profita : Komunikasi Ilmiah Akuntansi dan Perpajakan, 2021)
Financial performance is a description of the company's financial condition which can be analyzed using financial ratios. This study aims to examine the implications of corporate governance, company size and intellectual capital on the financial performance of food and beverage companies. Corporate governance is measured using the size of the board of commissioners and the board of directors. Company size is measured using total assets, and Intellectual Capital is measured using the VAICTM.method. The dependent variable, namely financial performance, is measured using Return on Assets (ROA). This research was conducted in food and beverages companies listed on the IDX in 2014–2017 using 48 research samples. The research method uses multiple linear regression analysis by partially testing the variables. The results showed that the size of the board of commissioners had a significant positive effect and the board of directors had a significant negative effect on financial performance, while company size and intellectual capital had no significant effect on financial performance.